(untitled) (Journal of the College of Basic Education, 2022)
Energy is the main source of the economy of the Caucasus countries in general and the Azerbaijani economy in particular, especially after the collapse of the Soviet Union and the independence of those countries that sought to use that energy to advance their economic reality by making energy the main engine of their foreign relations. Energy is the main source of the economy of the Caucasus countries in general and the Azerbaijani economy in particular, especially after the collapse of the Soviet Union and the independence of those countries that sought to use that energy to advance their economic reality by making energy the main engine of their foreign relations. الطاقة هي المصدر الرئيسي لاقتصاد دول القوقاز بشكل عام والاقتصاد الأذربيجاني بشكل خاص ، خاصة بعد انهيار الاتحاد السوفيتي واستقلال تلك الدول التي سعت لاستخدام تلك الطاقة للنهوض بواقعها الاقتصادي من خلال جعل الطاقة المحرك الرئيسي لعلاقاتهم الخارجية. Energy constitutes the main source for the economy of the Caucasus countries in general and the Azerbaijani economy in particular, especially after the collapse of the Soviet Union and the independence of those countries that sought to use that energy to advance their economic reality by making energy the main engine of their foreign relations. تشكل الطاقة المصدر الرئيسي لاقتصاد دول القوقاز بشكل عام والاقتصاد الأذربيجاني بشكل خاص ، خاصة بعد انهيار الاتحاد السوفيتي واستقلال تلك الدول التي سعت لاستخدام تلك الطاقة للنهوض بواقعها الاقتصادي من خلال جعل الطاقة المحرك الرئيسي لعلاقاتهم الخارجية. يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... The collapse of the Soviet Union is considered the restoration of the independence of Azerbaijan again, which during 1918-1920 was an already existing republic However it was crushed by the Soviets and the ambitions of the Bolshevik government. However it was crushed by the Soviets and the ambitions of the Bolshevik government. ومع ذلك تم سحقها من قبل السوفييت وطموحات الحكومة البلشفية. It was however crushed by the Soviets and the ambitions of the Bolshevik government. ومع ذلك تم سحقها من قبل السوفييت وطموحات الحكومة البلشفية. يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... Azerbaijan is one of the world’s oil-rich regions, which makes it attractive to foreigners and investments. Azerbaijan is one of the world’s oil-rich regions, which makes it attractive to foreigners and investments. أذربيجان هي إحدى مناطق العالم الغنية بالنفط ، مما يجعلها جاذبة للأجانب والاستثمارات. Azerbaijan is a global oil-rich region, which makes it attractive to foreigners and investments. أذربيجان منطقة عالمية غنية بالنفط ، مما يجعلها جذابة للأجانب والاستثمارات. يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... Its geographical location, which is located at a turning point between the West and the East, and being a neighbor to Russia, Iran,Turkey, Georgia, Kazakhstan and Turkmenistan, imposed on it the establishment of diplomatic relations with those countries, especially since all of those countries were coveting to obtain Azerbaijani energy resources, especially after their independence, as well as the direction of the United States Its geographical location, which is located at a turning point between the West and the East, and being a neighbor to Russia, Iran, Turkey, Georgia, Kazakhstan and Turkmenistan, imposed on it the establishment of diplomatic relations with those countries, especially since all of those countries were coveting to obtain Azerbaijani energy resources, especially after their independence, as well as the direction of the United States موقعها الجغرافي ، الذي يقع عند نقطة تحول بين الغرب والشرق ، وكونها جارة لروسيا وإيران وتركيا وجورجيا وكازاخستان وتركمانستان ، فرض عليها إقامة علاقات دبلوماسية مع تلك الدول ، خاصة وأن الجميع من تلك الدول كانت تطمع في الحصول على موارد الطاقة الأذربيجانية ، خاصة بعد استقلالها ، وكذلك اتجاه الولايات المتحدة Its geographical location, which is located at a turning point between the West and the East, and being a neighbor to Russia, Iran, Turkey, Georgia, Kazakhstan and Turkmenistan, imposed upon it the establishment of diplomatic relations with those countries, especially since all those countries were coveting to obtain Azerbaijani energy resources, especially after their independence, as well as the direction of the United States موقعها الجغرافي ، الذي يقع عند نقطة تحول بين الغرب والشرق ، وكونها جارة لروسيا وإيران وتركيا وجورجيا وكازاخستان وتركمانستان ، فرض عليها إقامة علاقات دبلوماسية مع تلك الدول ، خاصة وأن الجميع كانت تلك الدول تتوق للحصول على موارد الطاقة الأذربيجانية ، خاصة بعد استقلالها ، وكذلك اتجاه الولايات المتحدة يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... The United States is moving towards it with the aim of relying on its resources, which are located in the Caspian Sea. Therefore, one of the reasons for choosing the topic is to clarify the impact of energy and its role in drawing up the foreign policy of Azerbaijan’s foreign relations. Therefore, one of the reasons for choosing the topic is to clarify the impact of energy and its role in drawing up the foreign policy of Azerbaijan’s foreign relations. لذلك ، فإن أحد أسباب اختيار الموضوع هو توضيح تأثير الطاقة ودورها في رسم السياسة الخارجية للعلاقات الخارجية لأذربيجان. Therefore, one of the reasons for choosing this topic is to clarify the impact of energy and its role in drawing up the foreign policy of Azerbaijan’s foreign relations. لذلك ، فإن أحد أسباب اختيار هذا الموضوع هو توضيح تأثير الطاقة ودورها في رسم السياسة الخارجية للعلاقات الخارجية لأذربيجان. يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... The study attempts to test the validity of the following hypothesis, which is that the state that owns energy resources is the focus of the attention and greed of the major countries, and that the research objectives are to clarify that energy is a source for directing the external relations of the countries that own it and how to exploit those resources in dealing with the major countries, The year 1993 was chosen, the period that witnessed the emergence of international oil companies to obtain the right to explore, and it was the year of Azerbaijan’s transformations towards energy to determine its foreign policy through Heydar Aliyev’s rule until the end of his rule. The year 1993 was chosen, the period that witnessed the emergence of international oil companies to obtain the right to explore, and it was the year of Azerbaijan’s transformations towards energy to determine its foreign policy through Heydar Aliyev’s rule until the end of his rule. تم اختيار عام 1993 ، الفترة التي شهدت ظهور شركات النفط العالمية للحصول على حق الاستكشاف ، وكان عام تحولات أذربيجان نحو الطاقة لتحديد سياستها الخارجية من خلال حكم حيدر علييف حتى نهاية حكمه. The year 1993 was chosen, the period that witnessed the emergence of international oil companies to obtain the right to explore and it was the year of Azerbaijan’s transformations towards energy to define its foreign policy through Heydar Aliyev’s rule until the end of his rule. تم اختيار عام 1993 ، الفترة التي شهدت ظهور شركات النفط العالمية للحصول على حق الاستكشاف ، وكان عام تحولات أذربيجان نحو الطاقة لتحديد سياستها الخارجية من خلال حكم حيدر علييف حتى نهاية حكمه. يتعذّر تحميل النتائج بالكامل. إعادة المحاولة جارٍ إعادة المحاولة... جارٍ إعادة المحاولة... The results of the research, which included the importance of countries’ exploitation of their economic resources in directing their foreign policy to serve their internal and external interests